Diversities of Students’ Learning Style in Discovery Learning Method and Their Ability in Physics Problem Solving - Musyarrof, Ahmad Fatih; Nugroho, Sunyoto Eko; Hartono, Hartono; Masturi, Masturi (Unnes Science Education Journal, 2020)
The concept of physics can be understood through learning activities. Everyone has their own learning styles. For students, teaching and learning activities in the classroom physics with certain learning methods will slightly affect their learning styles. This article is intended to describe how students' learning styles in physics teaching and learning activities that required by certain learning methods. The subjects used were 66 students of Temanggung senior high school at grade 11 who were taught with the Discovery-Learning teaching method. Learning styles that used to classify are Honey-Mumford learning styles. The learning style is divided into 4 groups: Activists, Reflectors, Theorists, and Pragmatists. As the result, most students belong to the reflector learning styles.